ANALISIS PENGARUH CUSTOMER EXPERIENCE DAN KEPUASAN KONSUMEN TERHADAP MINAT BELI ULANG DI STORIA CAFFE MMXVI - Safitri, Koko (Jurnal Terapan Manajemen dan Bisnis, 2017)
Based on the purpose of this study is to analyze the relationship patterns between research variables, so that this study can be grouped as correlational research which will eventually be explained in detail the model formed as a picture and the extent to which relationships among variables affect each other. Therefore, this research will be supported by qualitative information to support the results of quantitative analysis. Sampling in this study was done randomly based on certain criteria of respondents who had eaten in Storia Caffe MMXVI. Sampling is intended to obtain an overview of the population by taking some of the population. Some of these populations are expected to represent the overall picture of the population. Population sampling is done randomly but in accordance with the ease of the researcher or convenience sampling.Based on the results of this study indicate that the variable Customer Experience and Consumer Satisfaction variables affect the variable Re-Purchase Intention and Customer Experience variables affect the variable Consumer Satisfaction because all variables are < p value (0.05). These results were tested using Amos Software with SEM analysis techniques.